Molecular docking‐guided synthesis of NSAID–glucosamine bioconjugates and their evaluation as COX‐1/COX‐2 inhibitors with potentially reduced gastric toxicity. (28th May 2021) - Jones Lipinski, Rachel A.; Thillier, Yann; Morisseau, Christophe; Sebastiano, Christopher S.; Smith, Brian C.; Hall, C. Dennis; Katritzky, Alan R.
Abstract: Non‐steroidal anti‐inflammatory drugs (NSAIDs) are a powerful class of inhibitors targeting two isoforms of the family of cyclooxygenase enzymes (COX‐1 and COX‐2). While NSAIDs are widely used in the management of pain, in particular as a treatment for osteo‐ and rheumatoid arthritis, their long‐term use has been associated with numerous on‐ and off‐target effects. As the carboxylic acid moiety present in common NSAIDs is responsible for some of their adverse effects, but is not required for their anti‐inflammatory activity, we sought to mask this group through direct coupling to glucosamine, which is thought to prevent cartilage degradation. We report herein the conjugation of commonly prescribed NSAIDs to glucosamine hydrochloride and the use of molecular docking to show that addition of the carbohydrate moiety to the parent NSAID can enhance binding in the active site of COX‐2. In a preliminary, in vitro screening assay, the diclofenac‐glucosamine bioconjugate exhibited 10‐fold greater activity toward COX‐2, making it an ideal candidate for future in vivo studies. Furthermore, in an intriguing result, we observed that the mefenamic acid‐glucosamine bioconjugate displayed enhanced activity toward COX‐1 rather than COX‐2. Abstract : A series of non‐steroidal anti‐inflammatory drugs were conjugated to glucosamine and evaluated for their in vitro activity against COX‐1 and COX‐2. Molecular docking studies suggest that the addition of a carbohydrate moiety to the drug can enhance binding in the active site of COX2.